OP0266 Monoclonal Antibodies Derived from Single CD19+ Synovial B Cells of RA Patients with Tertiary Lymphoid Structures Display Preferential Immunoreactivity towards Citrullinated Proteins of Nets. (10th June 2014) - Corsiero, E.; Carlotti, E.; Pratesi, F.; Wardemann, H.; Robinson, W.; Migliorini, P.; Pitzalis, C.; Bombardieri, M.
Abstract : Background: Rheumatoid arthritis (RA) is characterised by breach of self-tolerance towards citrullinated proteins. Up to 50% of RA patients display synovial tertiary lymphoid structures (TLS) with functional B cell follicles supporting a germinal-centre response and local autoantibody production [1]. The nature of the main (auto)antigenic reactivity of synovial B cells is unknown. Objectives: To characterize the autoreactive specificity at single cell level of synovial B cells isolated from TLS+ RA synovium. Methods: Single CD19+ B cells were FACS sorted from fresh synovial cell suspension of 3 TLS+ RA joints. RNA was used to amplify Ig VH and VL genes separately and PCR products were cloned and expressed as recombinant monoclonal antibodies each displaying identical specificity of the original B cell [2]. We obtained 139 individual VH sequences (33% IgM, 40% IgG, 27% IgA) and 175 VL sequences. Recombinant monoclonal antibodies were generated from a total of 66 matching H+L chains. Monoclonal antibodies were first screened for their immunoreactivity using a RA autoantigen microarray platform [3]. Immunoreactivity was then confirmed by Luminex, ELISA and WB towards specific citrullinated antigens and by cell-based immunoassays. 30 monoclonal antibodies derived from peripheral naïve or memory B cells of patients with primary Sjogren's syndrome were used as controls. Results: VH and VL mutational analysis demonstrated evidence of antigen-driven selection and intra-synovial clonal diversification. Interestingly, IgA clones displayed the highest mutational load followed by IgG and IgM. Among >300 RA autoantigens, the strongest and most frequent immunoreactivity was observed towards citrullinated histones H2A and H2B (∼30% of all RA B cell clones), followed by citrullinated vimentin. Selective reactivity towards the citrullinated but not unmodified forms of H2A, H2B and H4-derived histone peptides was confirmed by ELISA. The intensity of reactivity was directly correlated on the degree of the VH mutations and was abrogated by reverting hypermutated clones to germline sequences by reverse PCR. Citrullinated histones and vimentin are generated during neutrophil extracellular traps (NETs) formation. Indeed, WB on NET protein extracts confirmed selective reactivity towards a 14kDa band corresponding to histones H2/H4. Furthermore, immunofluorescence on neutrophils undergoing PMA-induced NETosis demonstrated specific reactivity of RA clones towards NETs but not resting neutrophils. Conclusions: Here we provide evidence for the first time that highly mutated, locally differentiated B cells isolated from RA synovial germinal centre-like structures display strong immunoreactivity towards citrullinated proteins generated during NETosis, primarily citrullinated histones. Thus, synovial NETs emerge as the main antigenic force driving in situ autoreactive B cell activation, selection and differentiation within ectopic germinal centre-like structures sustaining the humoral autoimmune response within the RA joints. References: Humby F et al., PLoS Med, 2009. Wardemann H et al., Science, 2003 Robinson, WH et al., Nat Med, 2002. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4422